Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1007/bf02522689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary heated fats on rat liver enzyme activity

Abstract: The objective of this study was to evaluate the effects of dietary heated fats from a commercial deep-fat frying operation on rat liver enzyme activity. The fats, partially hydrogenated soybean oil (PHSBO) used for four days and for 7 days (7-DH) for frying foodstuffs in a commercial restaurant, were fed to rats in either free access to food or by pair-feeding graded doses. All diets were isocaloric and contained 15 g/100 g of diet. Experiments were conducted with control rats fed non-heated (NH) PHSBO diet. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The latter may be nonvolatiles or volatiles retained in the oil which have been shown to be the only toxic materials in experiments with animal probes [23]. It seems that these substances might be the only concern as far as abused frying fats and oils are affected [12]. Further examinations of MPMs to identify their chemical structure(s) and to estimate their biological activity are in progress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may be nonvolatiles or volatiles retained in the oil which have been shown to be the only toxic materials in experiments with animal probes [23]. It seems that these substances might be the only concern as far as abused frying fats and oils are affected [12]. Further examinations of MPMs to identify their chemical structure(s) and to estimate their biological activity are in progress.…”
Section: Resultsmentioning
confidence: 99%
“…But nevertheless, the unequivocal health harm of TPMs has not been proved [11]. Cyclic monomeric frying by-products have been reported to interfere with the function of metabolic enzymes [12], but their toxicity could not be confirmed; and other compounds of unknown structures may be responsible for the observed toxicity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Lamboni and Perkins (19) reported that rats fed the 7-DH diet grew at a slightly slower rate than those fed CFAME. This may be due to the oxidation products generated in the oil upon heating since the CFAM group of rats grew less than control animals but more than the group of rats fed 7-DH diet.…”
Section: Discussionmentioning
confidence: 98%
“…All animals (10 animals in each group) were then assigned into three groups: a control group of rats [nonheated (NH)] fed a diet containing nonheated PHSBO and two experimental groups fed diets containing either PHSBO used 7 d for frying foodstuffs (7-DH) or CFAME. The animals were randomly assigned as previously described (19). Animals were sacrificed by decapitation with a guillotine after a 12-h fast.…”
mentioning
confidence: 99%
“…Feed efficiency and body weight gain in rats fed the OF and OFE diets were significantly lower than in those fed the CO diet. Liver weight and liver relative body weight in the OF and OFE groups were significantly higher than in the CO group (Table 3), results often observed in OFO-fed rats [8,22,23]. Vitamin E status and lipids As shown in Table 4, plasma α-tocopherol levels and the molar ratio of α-tocopherol to triglyceride in the plasma were significantly lower in groups OF and OFE than in group CO. Two-fold higher vitamin E levels in the diet did not result in significantly increased plasma α-tocopherol levels (OFE group compared to the OF group).…”
Section: Animal Growth and Food Intakementioning
confidence: 66%